1995
DOI: 10.1021/bi00028a040
|View full text |Cite
|
Sign up to set email alerts
|

Detection of internal and overall dynamics of a two-atom-tethered spin-labeled DNA

Abstract: DNA motions consist of several components which couple, making their investigation difficult. This study describes an approach for obtaining dynamical information by EPR when spin-labeled nucleic acids are examined. The analysis is accomplished by implementing two motional models. The first model (i.e., dynamic cylinder model) views the spin-labeled helix as a diffusing cylinder containing internal dynamics which are characterized by an order parameter. The second model (i.e., base disk model) provides correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…The Bobst group developed a base disk model, in which the spin-labeled base is considered an axially symmetric diffusing system (25,29). The principle motion is characterized by two correlation times: τ ‖ describes rotational diffusion about the principle axis as defined by the average position of the bonds that connect the base to the nitroxide, and τ ⊥ describes the motion about the axis perpendicular to the tether bond.…”
Section: Spectral Simulations In the Slow-motionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Bobst group developed a base disk model, in which the spin-labeled base is considered an axially symmetric diffusing system (25,29). The principle motion is characterized by two correlation times: τ ‖ describes rotational diffusion about the principle axis as defined by the average position of the bonds that connect the base to the nitroxide, and τ ⊥ describes the motion about the axis perpendicular to the tether bond.…”
Section: Spectral Simulations In the Slow-motionmentioning
confidence: 99%
“…The mean-square oscillation amplitude is directly related to the order parameter, but the simulation does not produce any estimation of the correlation time for the internal dynamics. For nitroxides that are more flexibly attached to bases within a DNA duplex (e.g., Table I, entry 5), the Bobst group has taken a similar approach and developed a dynamic cylinder model (29), which yields an order parameter that describes the amplitude of the nitroxide motion. It was suggested that the order parameter reports on both the base dynamics and the motion of the nitroxide with respect to the base.…”
Section: Spectral Simulations In the Slow-motionmentioning
confidence: 99%
See 3 more Smart Citations